Notwehr and Rache: quale possibile ‘diritto’ alla resistenza nell’Abstraktes Recht? - Magni, Chiara (B@belonline, 2022)
Starting from the recent studies of K. Vieweg and M. Pawlik, who identify the Hegelian reason for self-defence in the concept of zweiter Zwang, we aim to show how, in terms of the abstraktes Recht, there are in fact insufficient theoretical elements to distinguish self-defence from revenge – which invalidates the supposed Hegelian justification of Notwehr. (i) We will start by briefly analyzing the results that the Notwehrdogmatik of the Hegelian tradition produced throughout the 19th century, in order to show retrospectively how the conceptual determinations elaborated by these authors (including the difference between Notwehr and Rache/Strafe) do not find confirmation in Hegel. (ii) In a second step, we will discuss whether a form of ‘resistance’ as a sacrifice of the will (§§ 90, 91 and 92 of the Elements of the Philosophy of Right) can rather be asserted as far as the abstraktes Recht is concerned; a comparison with Fragment 55 of Hegel’s Early Writings seems, however, to deny the ‘juridical’ adequacy of this figure.